Carfilzomib associated thrombotic microangiopathy initially treated with therapeutic plasma exchange. Issue 5 (21st November 2014) - Sullivan, Matthew R.; Danilov, Alexey V.; Lansigan, Frederick; Dunbar, Nancy M.
<x xml:space="preserve">Abstract</x> Drug associated thrombotic microangiopathy (TMA) is a rare event causing thrombocytopenia, microangiopathic anemia, renal failure, and neurologic abnormalities. Here, we present a case of TMA that occurred during the first cycle of treatment with carfilzomib for relapsed multiple myeloma. J. Clin. Apheresis, 2014. © 2014 Wiley Periodicals, Inc.